A min-max inventory management study on XYZ Corporation - Alberto, Quirby Angelo S.; Atanacio, Brian David M.; Cucueco, Cyrill S.; Mercado, Ana P.
A trading company must have an efficient inventory system to increase customer satisfaction through the minimization of lead time from the customer's perspective. The study investigates on the 123 out of the 222 fast moving items of XYZ, Corporation that currently do not have Minimum and Maximum stock levels set. |With this in mind, the company is compelled to order from its suppliers only after the receipt of orders from their customers. Establishing the mentioned parameters of these items will reduce the company's current average customer lead time of 50 days by at least 31 days to match the company's target average customer lead time. Classifying the fast moving items into ABC categories and setting the desired service level for each category ensured that that the items with the highest annual peso value had the smallest stock-out risk. With the information on the demand, lead time, desired service level, and costings, the Minimum and Maximum stock levels were then set per item. The minimum was simply determined by calculating each item's Reorder Point (ROP), whereas, two techniques were used to compute for the Maximum- first, using the addition of Economic Order Quantity (EOQ) to the ROP, and the second, as a function of stability. Per item, the Maximum stock level that yielded a lower inventory cost, but at the same time satisfying the set theoretical service level, was chosen in order to guarantee minimization of stock-outs with simultaneous financial consideration. Afterwards, simulations were conducted to test the actual service level using the calculated Minimum and selected maximum stock levels. Proper validation of the established parameters of XYZ Corporation's 123 items enabled the reduction of the average customer lead time from the current 50 days to only 17 days, resulting to an increase in customer satisfaction and a more efficient inventory system.